Customer satisfaction in ISO 9001 certified and non-ISO 9001 certified Higher Education Institution (HEI) libraries in Central Luzon - Tongol, Reyma R. (School of Library and Information Studies, University of the Philippines Diliman, 2015)
The study aimed to find the significant difference in the level of customer satisfaction between ISO 9001 and non-ISO 9001 certified HEI libraries in Central Luzon using the Libqual+TM service quality dimensions: Effect of Service, Information Control and Library as a Place. It also aimed to find out the current level of customer satisfaction with the ISO 9001 and the non-ISO 9001 certified HEI libraries in Central Luzon.